2022
DOI: 10.1002/mmce.23052
|View full text |Cite
|
Sign up to set email alerts
|

SLA printed horn antenna with filtering network based on dual‐mode ellipsoid resonator

Abstract: This paper presents a horn antenna with a 5th-order dual-mode ellipsoid resonator filtering network, fabricated by stereo lithography apparatus 3-D printing technic. The filtering part employs two dimpled ellipsoid dual-mode resonators, operating at the fundamental TM 101 mode. Compared to the filters employing cylindrical resonators with tuning posts, the proposed filtering network is with lower loss (due to the high Q u resonator) and the performance is less sensitive to the fabrication errors. The antenna w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, SLA has been widely used in manufacturing dental prostheses by Yoo et al [ 9 ], and the overall 3D accuracy of all 3D-printed resin models showed clinically acceptable ranges. A horn antenna with a 5th-order dual-mode ellipsoid resonator filtering network was developed by Liang et al [ 10 ] through SLA, which achieved a lower loss and higher measured gain of antenna function. Zhao et al [ 11 ] fabricated the periodical and ordered polymer–nickel-coated composite materials with a diamond-structure microlattice and various contents of phosphorus via electroless nickel–phosphorus (Ni–P) coating onto the diamond-structured polymeric templates using SLA, the maximum compressive strength of which was 2.1 times higher than that of polymer templates.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SLA has been widely used in manufacturing dental prostheses by Yoo et al [ 9 ], and the overall 3D accuracy of all 3D-printed resin models showed clinically acceptable ranges. A horn antenna with a 5th-order dual-mode ellipsoid resonator filtering network was developed by Liang et al [ 10 ] through SLA, which achieved a lower loss and higher measured gain of antenna function. Zhao et al [ 11 ] fabricated the periodical and ordered polymer–nickel-coated composite materials with a diamond-structure microlattice and various contents of phosphorus via electroless nickel–phosphorus (Ni–P) coating onto the diamond-structured polymeric templates using SLA, the maximum compressive strength of which was 2.1 times higher than that of polymer templates.…”
Section: Introductionmentioning
confidence: 99%